2013
DOI: 10.1016/j.hydromet.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Uranium stripping from tri-n-butyl phosphate by hydrogen peroxide solutions

Abstract: a b s t r a c t a r t i c l e i n f oThe processes of uranium stripping from 30% tri-n-butyl phosphate (TBP) in "odorless" kerosene by H 2 O 2 solutions both with and without NH 4 OH added were investigated in the temperature range of 20-50°C and with a volumetric ratio of 1 between the organic and aqueous phases. The uranium was selectively precipitated in the form of uranium peroxide during stripping from the organic phase by hydrogen peroxide. The stripping of uranium increased with increasing H 2 O 2 conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Thus, the contents of hydrofluoric acid and hydrazine in the stripping solution are the major parameters that influence the extent of uranium precipitation. A study (Smirnov et al, 2013) showed that increasing the contact time of the phases increases the degree of uranium precipitation from the organic phase. Therefore, the effect of the phase contact time after stirring (i.e., the holding time) on uranium stripping from TBP was studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the contents of hydrofluoric acid and hydrazine in the stripping solution are the major parameters that influence the extent of uranium precipitation. A study (Smirnov et al, 2013) showed that increasing the contact time of the phases increases the degree of uranium precipitation from the organic phase. Therefore, the effect of the phase contact time after stirring (i.e., the holding time) on uranium stripping from TBP was studied.…”
Section: Resultsmentioning
confidence: 99%
“…The application of hydrogen peroxide or ammonium carbonate solutions for stripping from loaded TBP results in the precipitation of uranium in the form of uranium peroxide or ammonium uranyl tricarbonate, respectively, which can readily be converted to UO 3 (Chegrouche and Kebir, 1992;Singh and Gupta, 2000;Smirnov et al, 2013). The operations of evaporation and denitration can be also eliminated by the use of the precipitation method.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of hydrogen peroxide on the organic phase was studied by IR spectroscopy. 78 The organic cerium deposits were obtained by a stripping precipitation method from cerium-loaded P507 organic phase using oxalic acid as a precipitating agent and nano-sized ceria particles were prepared by calcining the products at 500°C.…”
Section: Kinetics Of Stripping By Precipitationmentioning
confidence: 99%
“…Como lo que se busca es alterar ese equilibrio para obtener la precipitación de uranio. Uno de los posibles agentes precipitantes según SMIRNOV et al [2] puede ser el peróxido de hidrógeno (H 2 O 2 ) en exceso estequiométrico en condiciones de pH débilmente ácidos.…”
Section: Introductionunclassified